2017
DOI: 10.1038/s41598-017-02907-6
|View full text |Cite
|
Sign up to set email alerts
|

VEGF-A Stimulates STAT3 Activity via Nitrosylation of Myocardin to Regulate the Expression of Vascular Smooth Muscle Cell Differentiation Markers

Abstract: Vascular endothelial growth factor A (VEGF-A) is a pivotal player in angiogenesis. It is capable of influencing such cellular processes as tubulogenesis and vascular smooth muscle cell (VSMC) proliferation, yet very little is known about the actual signaling events that mediate VEGF-A induced VSMC phenotypic switch. In this report, we describe the identification of an intricate VEGF-A-induced signaling cascade that involves VEGFR2, STAT3, and Myocardin. We demonstrate that VEGF-A promotes VSMC proliferation vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 45 publications
(59 reference statements)
1
19
0
Order By: Relevance
“…Among these predicted genes, we chose VEGFA and FGF1 for additional investigation. Previous studies have shown that VEGFA exerted enhanced effects on the VSMC proliferation as well as differentiation . In terms of FGF1, inhibition of FGF1 suppressed VSMC proliferation and migration, while overexpressed FGF1 in VSMCs exerted enhanced effects on cell proliferation and migration .…”
Section: Discussionmentioning
confidence: 86%
“…Among these predicted genes, we chose VEGFA and FGF1 for additional investigation. Previous studies have shown that VEGFA exerted enhanced effects on the VSMC proliferation as well as differentiation . In terms of FGF1, inhibition of FGF1 suppressed VSMC proliferation and migration, while overexpressed FGF1 in VSMCs exerted enhanced effects on cell proliferation and migration .…”
Section: Discussionmentioning
confidence: 86%
“…STAT3 signaling has been shown to be activated in skeletal muscle and promotes skeletal muscle atrophy in muscle diseases, such as Duchenne muscular dystrophy (DMD), and Merosin-deficient congenital muscular dystrophy (MDC1A), as well as cancer and sepsis [ 7 , 8 , 9 ]. In addition to skeletal muscles, STAT3 signaling has been shown to play critical roles in both vascular and central nervous systems, thus directly and indirectly contributing to muscle health [ 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…17 Notch3 is reported to play an important role in regulating the alveolar epithelium. 21,22 VEGFA inhibits cell apoptosis, stimulates endothelial cell migration and proliferation, and is widely expressed in highly vascularized organs such as lungs. 20 Vascular endothelial growth factor-A (VEGFA) is a potent multifunctional cytokine that has several effects on angiogenesis and is associated with COPD.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, Notch3 is identified as a target of miR‐206 in colorectal cancer cells, HeLa cells, and hepatocellular carcinoma cells . Vascular endothelial growth factor‐A (VEGFA) is a potent multifunctional cytokine that has several effects on angiogenesis and is associated with COPD . VEGFA inhibits cell apoptosis, stimulates endothelial cell migration and proliferation, and is widely expressed in highly vascularized organs such as lungs .…”
Section: Introductionmentioning
confidence: 99%